A Longitudinal Study of Physical and Mental Health and Health-Related Attitudes Among Music Students: Potentials and Challenges for University Health Promotion Programs - Rosset, Magdalena; Baumann, Eva; Altenmüller, Eckart (Frontiers in Psychology, 2022)
Objective: Well-being of music students has been an increasing matter of concern since studies show that up to 50 % of beginners suffer from playing-related pain or anxiety. The aim of this longitudinal study was to examine health status, health-related attitudes, behaviors, knowledge, skills, and coping strategies of students at the beginning of their education at a music university and at the end of their second semester. Methods: Based on a longitudinal online survey conducted among students at a German music university since 2017, we investigated mental and physical health status, health-related attitudes, knowledge, skills, behaviors, and coping strategies of music students at the beginning of their first year (n = 205). We analyzed differences between performance and music education majors and between students playing different main instruments. In a subsample (n = 62), we additionally analyzed changes between the beginning of the music students’ first and the end of their second semester, also depending on whether they attended courses on musicians’ health. Results: Music students are already in demand when they enter a music university, practicing on average almost three hours daily. Compared to other body regions, pain in shoulders/back is most prevalent in first-year students, especially in those playing string instruments. Performance majors reported better knowledge about health risks and protective measures for musicians, better coping abilities, and practiced more than music education majors. First-year students assessed their overall and mental health status at the beginning of their first semester mainly as good, but we found a decrease in mental health status at the end of the second semester. After two semesters, students attending courses on musicians’ health showed increased knowledge and skills regarding different aspects of musicians’ health. Conclusion: The health status of music students when they first enter a music university is still a concern. Information and practical courses enabling students to prevent overuse and cope with performing anxiety and other stressors are important components of a comprehensive study program. Knowledge about music students’ needs can help conservatories better respond to the requirements and develop courses and measures supporting students from the beginning of their education.